2014
DOI: 10.1080/09298215.2014.937724
|View full text |Cite
|
Sign up to set email alerts
|

The Rhythm Span Task: Comparing Memory Capacity for Musical Rhythms in Musicians and Non-Musicians

Abstract: The study introduces a rhythm memory task and compares performance of musicians and non-musicians. The rhythm span task with increasing and decreasing sequence length according to the participants' performance, measures the individual memory capacity for musical rhythms. Results show that musicians perform significantly better on the rhythm span task indicating that memory capacity for rhythms is superior after many years of formal musical training. Additionally performance correlates positively with an establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…A special case of sequence memory arises when time intervals themselves must be remembered. Most studies that investigate memory for sequences of durations test our ability to discriminate rhythms, that is, sequences of durations that are integer multiples of a discrete, quantised beat [ 47 ]. These have demonstrated a soft limit to the number of durations that can be remembered which is much greater than for non-rhythmic sequences.…”
Section: Stm For Timementioning
confidence: 99%
“…A special case of sequence memory arises when time intervals themselves must be remembered. Most studies that investigate memory for sequences of durations test our ability to discriminate rhythms, that is, sequences of durations that are integer multiples of a discrete, quantised beat [ 47 ]. These have demonstrated a soft limit to the number of durations that can be remembered which is much greater than for non-rhythmic sequences.…”
Section: Stm For Timementioning
confidence: 99%
“…Further segmentation studies should overcome methodological issues concerning the validity of the participant sample by including an established questionnaire, such as the Goldsmith's Musical Sophistication Index (Gold-MSI, see Müllensiefen, Gingras, Musil, & Stewart, 2014), which has been recently used for assessments in musicianship studies (Carey et al, 2015;Schaal, Banissy, & Lange, 2015). This can be helpful not only for comparing research findings but also for improving recruitment and classification: Gold-MSI takes into account that training may not determine musical abilities such as perception of form (Bigand & Poulin-Charronnat, 2006;Lalitte & Bigand, 2006), and also that some musical skills do not result from formal music training (Müllensiefen et al, 2014).…”
Section: Considerations For Future Researchmentioning
confidence: 99%
“…On the other hand, their training may enable professional musicians to employ different forms of mental representation of rhythms than non-musicians (Aleman et al, 2000;Palmer & Krumhansl, 1990;Schaal et al, 2014). Musicians could use forms of visuo-spatial representations to memorise rhythms because they have been trained to transfer rhythms into musical notation.…”
Section: Musical Training and Memory For Rhythmmentioning
confidence: 97%
“…Differences between musicians and non-musicians have received a fair bit of attention (Gaser & Schlaug, 2003;Koelsch, Schröger, & Tervaniemi, 1999;Musacchia, Sams, Skoe, & Kraus, 2007;Musacchia, Strait, & Kraus, 2008;Parbery-Clark, Skoe, Lam, & Kraus, 2009;Schaal, Banissy, & Lange, 2014;Zatorre, 1998), but it is unclear whether any effects of musical training will extend to differential processing in memory for rhythm. Several studies have shown superior performance on memory tasks by musicians (Jakobson, Lewycky, Kilgour, & Stoesz, 2008;Kilgour, Jakobson, & Cuddy, 2000;Schaal et al, 2014;Tervaniemi, Rytkönen, Schröger, Ilmoniemi, & Näätänen, 2001), which would indicate that musically trained subjects should exhibit generally superior performance at longer ISI than non-musicians, but whether this will affect memory for vocal versus clapstick rhythms is uncertain. Moreover, musical training may specifically improve memory for rhythm by fostering strategies such as categorisation of rhythmic intervals in terms of a set of learned duration values (e.g., quarter note, eighth note, etc.)…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation